انتظا ر حسین کی ناول نگاری میں اسلامی تہذیبی شعورRealization of Islamic Culture in Intizār Hussain's Novel Writing (Al-Qamar, 2021)
This paper studies the realization of Islamic culture in Intizār Hussain's Novel Writing. It argues in Intizār Hussain’s novels many centuries of Indian Islamic culture and its evolution seems to breathe. That’s why sensational appeal of these novels keep eternal colours out of which Islamic colour is deeply prominent. These novels can be considered such rainbow of Islamic Civilization that every color of it seems to express the meaning of Islamic Civilization and Culture and faith and functions. The deep sense of Islamic Civilization in these novels grants individuality to Intizār Hussain amongst the Novelists of the present era. He has used a fusion of declarative and symbolism that has increased the meaningfulness in his novels. The background technique of his novels is quite prominent.
Keywords: Islamic culture; realization; novels Intizār Hussain